Implementasi Decision Support System Dynamic Menggunakan Weight Product Untuk Menentukan Uang Kuliah Tunggal - Dyah Ayu Wiranti; Kurnia Siwi Kinasih; Ainafatul Nur Muslikah; Dyah Wardani; Agung Teguh Wibowo Almais (Department of Science and Technology Ibrahimy University, 2020)
Single tuition is the extension of the single tuition, which can be interpreted as a payment system made at the time of admission in both State and private colleges in Indonesia. Where this single tuition can provide benefits for the equitable of each student and help the students who are less able in terms of the economy that is certainly derived from the underprivileged family. In the calculation process determines the single tuition money each student needs a long process and time. So, there is an idea to implement a Decision Support System Dynamic (DSSD) so that at the time of determination of single tuition can be evenly and by the actual situation. One method that can be used on DSSD is the Weighted Product (WP) method. By implementing the method of WP combined with the concept of DSSD, then generated values of confusion matrix (recall, precision, f-measure, and accuracy) obtained by looking for the value of comparison between test data with pattern data. Obtained confusion matrix value with system testing and get the results Precision 88.89%, Recall 82.76%, Accuracy 77.14%, F-Measure 85.71%.